Discovery of a novel brown algal genus and species Setoutiphycus delamareoides (Phaeophyceae, Ectocarpales) from the Seto Inland Sea, Japan - Hiroshi Kawai (Nature Portfolio, 2021)
Abstract We describe a new genus and species of brown algae from the Seto Inland Sea, Japan. This species is similar to Delamarea in gross morphology and anatomy, but distinctive in having longer thalli with rare branching and shorter cortical cells. In culture, pluri-zoids derived from plurilocular zoidangia on the erect thalli developed into filamentous gametophytes bearing ectocarpoid plurilocular zoidangia, but also formed parenchymatous erect thalli of sub-sympodial growth similar to Trachynema often having branches, and formed lateral and terminal plurilocular zoidangia. Molecular phylogenies using concatenated chloroplast and mitochondrial gene sequences showed the new alga nested in the clade composed of ectocarpalean genera with diffuse growth, parenchymatous thalli, and multiple chloroplasts, but this species is distinctive. Therefore, we propose Setoutiphycus delamareoides gen. & sp. nov. for this new alga, and provisionally place it in Chordariaceae, Ectocarpales. The Seto Inland Sea repeatedly dried during sea level regressions during glacial periods, and the present sea level recovered after the last glacial maximums (LGM), ca. 10,000 years ago. Therefore, it is unlikely that the species evolved within this area. Its distribution in the area may be explained as a remnant population that survived in refugia in southern Japan during the LGM.